Developing a WELL building model for office environments - Tan, Carmen Y. M.; Abdul Rahimi, Abdul Rahman; Lee, Yong Siang (Springer, 2024)
Many reported cases of occupants in modern office buildings suffer from severe health risks, negative impacts on well-being, and productivity loss. Existing building standards often prioritize energy performance and green environments over human sustainability. Moreover, office buildings have a distinct group of occupants that require extra attention. Hence, the study aims to develop a WELL building model specifically for office buildings to support occupants’ well-being, health, and productivity (i.e., WELL). To achieve that objective, this study developed a list of physical indoor building features through a systematic literature review and semi-structured interviews. Then, the features were inserted into a survey and sent to office building occupants and built environment professionals. The collected data was analyzed using the analytic hierarchy process (AHP) and confirmatory factor analysis (CFA). The findings suggest twelve new features applicable for supporting WELL in office buildings: workspace privacy, sufficient space, office layout, cleanliness, efficiency in building services, individual control, building automation system, Information Technology (IT) infrastructure, Wireless Fidelity (WiFi) risk, security system, safety at parking lots, and safe design. Also, three new concepts for supporting WELL in office buildings were established: office space, building services and maintenance, and smart systems. The new concepts and features lay a foundation for designing office buildings that comprehensively target occupants’ WELL. Finally, this study is unique as it accentuates the development of a WELL building model specifically for office buildings.